Pengaruh Substitusi Pati Ganyong (Canna Edulis Kerr) Terhadap Mutu Sensoris Tartlet - Viona Monty Aprillya; Guspri Devi Artanti; Mariani (Program Studi Tata Boga Universitas Negeri Jakarta, 2020)
This study aims to the effect of canna starch substitutes (Canna Edulis Kerr) with the sensory quality of the tartlets skin senses devouring aspects of color, taste, aroma and texture. This research was carried out in the Pastry dan Bakery Laboratory, Food and Nutrition Program, Faculty of Engineering, State University of Jakarta. This research was conducted a tartlet laboratory test with the analysis of the properties of water content and ash content. Then the sensory quality assesment carried out organoleptic tests conducted on 45 rather trained panelists. This research is using experimental method. The population in this study was the tartlet with the canna starch subtitution, while the sample was the skin of tartlet substitution canna starch with the percentage of 20%, 40% and 30%. Based on deskriptive analysis, the results of the tartlet hypotesis test analysis with 40% canna starch substitution have the highest average of 4,9, which is the criteria for cream color. In the taste aspect, tartlet with a starch substitution of 20% and 30% has the highest average of 3,7, which is the criteria of sweet taste. In the aspect of aroma, tartlet with 40% canna starch substitution has the highest average of 4,1, which is in the criteria flavor not have a canna scent. And in the aspect of texture, tartlet with 30% dan 40% canna starch substitution has the highest average of 4,3, which is on crispy teksture. Kruskal Wallis Test results showed no significant substitution effect of canna starch on the sensory quality of tartlet.